A mathematical model for supply demand matching in a low carbon electricity system. Issue 5 (2nd September 2016) - Amrutha, A. A.; Mathirajan, M.; Balachandra, P.
Abstract: In this study, the research problem of "optimally supply electricity from the existing supply options and considering non-supply options as well as future supply options in the presence of low carbon technology and emission policy interventions to minimize the overall economic costs and emission costs" is addressed. The problem is addressed in the supplyside management aspect of electricity planning. Three mathematical models are created step-by-step to propose a complete Mixed-integer Linear Programming (MILP) model for the defined research problem. A LINGO set code has been developed to generate the proposed MILP model for any given data. For validating the model, a suitable data is collected from the Karnataka Electricity System. Using this data, the proposed three models are generated and solved using LINGO. The results obtained on these three models are analyzed.